2008
DOI: 10.1152/ajpcell.00491.2007
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone increases expression and activity of multidrug resistance transporters at the rat blood-brain barrier

Abstract: Narang VS, Fraga C, Kumar N, Shen J, Throm S, Stewart CF, Waters CM. Dexamethasone increases expression and activity of multidrug resistance transporters at the rat blood-brain barrier. Am J Physiol Cell Physiol 295: C440 -C450, 2008. First published June 4, 2008 doi:10.1152/ajpcell.00491.2007.-Brain edema is an important factor leading to morbidity and mortality associated with primary brain tumors. Dexamethasone, a synthetic glucocorticoid, is routinely prescribed with antineoplastic agents to alleviate pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
103
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 43 publications
(47 reference statements)
7
103
2
1
Order By: Relevance
“…This is in contrast to other substrates of P-gp such as dexamethasone and ritonavir (Gutmann et al, 2006;Narang et al, 2008;Perloff et al, 2004).…”
Section: And R-citalopram and Its Metabolites In Abcb1ab (-/-) Knocmentioning
confidence: 73%
“…This is in contrast to other substrates of P-gp such as dexamethasone and ritonavir (Gutmann et al, 2006;Narang et al, 2008;Perloff et al, 2004).…”
Section: And R-citalopram and Its Metabolites In Abcb1ab (-/-) Knocmentioning
confidence: 73%
“…In addition to PXR, other nuclear receptors are also expressed at the blood-brain barrier, where they control regulation of several transporters. Narang et al (2008) demonstrated that dexamethasone activation of the glucocorticoid receptor increased P-glycoprotein, Mrp2, and BCRP in rat brain endothelial cells and showed that PXR activation with PCN increased BCRP expression. In this context, the present study adds another mosaic to the picture that is emerging for the blood-brain barrier, that is, like in liver (Rosenfeld et al, 2003), a complex network of nuclear receptors controlling metabolizing enzymes and drug efflux transporters.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, gene amplification (Ross et al, 1999;Knutsen et al, 2000;Volk et al, 2002) has been shown to be an important mechanism for elevated ABCG2 expression in drug-resistant cancer cells. Recent studies have demonstrated that transcriptional factors [i.e., nuclear receptors (Ee et al, 2004b;Ebert et al, 2005;Szatmari et al, 2006;Honorat et al, 2008;Narang et al, 2008;Vore and Leggas, 2008;Wang et al, 2008b) and epigenetic factors Turner et al, 2006;Calcagno et al, 2008;Nakano et al, 2008;To et al, 2008a)] play important roles in the regulation of ABCG2 in different model systems. Potential regulation of ABCG2 at its 3Ј-untranslated region (3Ј-UTR) is just beginning to be explored .…”
mentioning
confidence: 99%